(3WHbGJ GdMfajIs - (3TeSj LdHjs
(3ChdgG (B:s
(3GdMeO ddg agPG cJGH eNJUQ aj PcQ WHbGJ GdMfajI PcQJ ajg GdeTGgjQ ef GdCFeI GdPjf fbdhG Yde GdTQjYI aj cd WHbI hfTQhgG Hjf GdCeI eY SdSdJge Ydi WHbGJge hCMhGdge Ydi OQLGJge GdCbOe aGdCbOe s
(3BNQgG (B:s
(3Ke GfJbd Edi WHbI Gdehdi CMeO Hf ceGd HGTG hMjO YUQg CNP Yf ehdGfG SfGf HGTG hehdGfG dWaj Jhaj SfI CQHYjf hJSYeGFI QhM Gddg JYGdi CQhGMge Je s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdJGQjNs